The Influence of Hyper Content-Based Practicum Guidance on Students' Scientific Literacy Ability in Material Structure and Function of Plant Tissues for Class XI IPA Students at SMA Negeri 2 Gowa - Sri Rahayu (JED (Jurnal Etika Demokrasi), 2021)
This research is an experimental researchQuasi Experimental Design which aims to determine the effect of a practicum-based guidehyper content on the scientific literacy skills of class XI IPA students at SMA Negeri 2 Gowa on the material structure and function of plant tissue with a research design "Nonequivalent Control Group Design”. The population in this study was class XI IPA SMA Negeri 2 Gowa which consisted of six classes with a total of 151 students. The sample of this study consisted of two classes, namely class XI IPA 1 as an experimental class of 25 students and class XI IPA 2 as a control class of 25 students who were randomly selected.Simple Random Sampling. The research variables consist of independent variables, namely practicum-based guideshyper content while the dependent variable is scientific literacy ability. Data collection is done through givingpretest andposttest. Data were analyzed with descriptive statistics and inferential statistics with the help ofSPSS (Statistical Product and Service Solutions) versi 25. The results showed that the average value of the resultsposttest the experimental class is 71.33 and the control class is 54.73. In the hypothesis test throughIndependent Sample T- Test with a value of p = 0.000 a = 0.05, it can be concluded that there is an influence of practicum-based guidancehyper content on students' scientific literacy skills on the material structure and function of plant tissue in class XI IPA SMA Negeri 2 Gowa.Penelitian ini merupakan penelitian eksperimen Quasi Experimental Design yang bertujuan untuk mengetahui pengaruh penuntun praktikum berbasis hyper content terhadap kemampuan literasi sains siswa kelas XI IPA SMA Negeri 2 Gowa pada materi struktur dan fungsi jaringan tumbuhan dengan desain penelitian “Nonequivalent Control Group Design”. Populasi dalam penelitian ini adalah kelas XI IPA SMA Negeri 2 Gowa yang terdiri dari enam kelas dengan jumlah total 151 siswa. Sampel penelitian ini sebanyak dua kelas yaitu kelas XI IPA 1 sebagai kelas eksperimen sebanyak 25 siswa dan kelas XI IPA 2 sebagai kelas kontrol sebanyak 25 siswa yang dipilih secara Simple Random Sampling. Variabel penelitian terdiri dari variabel bebas yaitu penuntun praktikum berbasis hyper content sedangkan variabel terikat yaitu kemampuan literasi sains. Pengumpulan data dilakukan melalui pemberian pretest dan posttest. Data dianalisis dengan statistik deskriptif dan statistik inferensial dengan bantuan SPSS (Statistical Product and Service Solutions) versi 25. Hasil penelitian menunjukkan bahwa pada nilai rata-rata hasil posttest kelas eksperimen 71,33 dan kelas kontrol yaitu 54,73. Pada uji hipotesis melalui Independent Sample T- Test dengan nilai p = 0,000 a = 0,05 dengan demikian dapat disimpulkan ada pengaruh penuntun praktikum berbasis hyper content terhadap kemampuan literasi sains siswa pada materi struktur dan fungsi jaringan tumbuhan siswa kelas XI IPA SMA Negeri 2 Gowa..